Pengembangan Sistem Pendukung Keputusan Penelusuran Minat Bakat Siswa SMP Dalam Memilih Jurusan di SMK Berbasis Web - Abdillah SAS; Andi Muh Akbar Saputra; Muh Fadli Fausi Sahlan (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2022)
The study aims at (1) designing the development of SPK (Decision Support System) of studens’ talent interests with web basis, (2) determining studens majors based on talents and interests, (3) designing the easier application, research population was the students of SMP who where about to graduate of students of SMK who were just accepted in the school. The SPK being built can determine the majors, learning styles, and personality of students based on the answers being questioned. Data colleting techniques used in this study were interview, literature review, and questionnaire. Data processing instruments of the study were structural equation modeling, black box testing, alpha, and beta testing. The results of the study reveal that the SPK of talents and interests with web basis can be designed and easier for the students in determining the majors at SMK because the SPK made had been tested fuctionality with very feasible category with the ttal percentage of 100%. Based on the usability test, this SPK is categorized as very good with the percentage of 100%. Based on the usability test, this SPK is categorized as very good with the percentage of 89.63%. Based on the result of SEM test by including various factors which were considered as influencing the saticfaction of SPK users, it is concluded that the factors of system quality, information quality, and interation quality influence the satisfaction of SPK users; wheres, the service quality has no influence of satisfaction to SPK users Keyword — decision support systems, majors in SMK, web applications, structural equation modeling.